Implementation of Civil Servant Discipline Policy at the Regional Staffing Agency of South Sulawesi Province - Nurhalifah; H, Herman; Nur, Andi Cudai; Haerul; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2024)
This study aims to explore the implementation of Civil Servant Discipline Policy at the Regional Civil Service Agency (Badan Kepegawaian Daerah) of South Sulawesi Province and identify the factors influencing its implementation. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data validity was ensured using source triangulation, while data analysis was conducted through data condensation, data presentation, and conclusion drawing.The findings reveal that the implementation of the Civil Servant Discipline Policy in the Regional Civil Service Agency of South Sulawesi Province has been effective in several aspects. (1) Standards and Policy Targets have been well applied, as indicated by employees' understanding of Government Regulation No. 94 of 2021 and the alignment of policy targets with field conditions. (2) Resources, including employee qualifications and infrastructure, support the effective implementation of the discipline policy, with tools such as digital attendance systems being utilized. (3) Organizational Characteristics of the implementing agency facilitate policy enforcement through structured internal coordination and supervision. (4) Inter-organizational Communication runs smoothly, although occasional challenges in inter-agency coordination exist. (5) Policy Implementers' Attitudes reflect high dedication, supported by a culture of discipline and transparency. (6) The Social, Economic, and Political Environment generally supports the policy’s execution, though political dynamics sometimes affect consistency.Supporting factors include strong leadership, a disciplined work culture, and the availability of necessary facilities and infrastructure. However, obstacles such as employees’ lack of awareness of existing regulations, inconsistent enforcement of sanctions, and differing interpretations of policies impede efficient information flow and policy implementation. Overall, the implementation of the Civil Servant Discipline Policy at the Regional Civil Service Agency of South Sulawesi Province has been effective, but several challenges require improvement to enhance its sustainability and impact.